Analisis Efisiensi Rumah Makan Waroeng Spesial Sambal "Ss" - Husaen, Yulianto, Ir Maulidyah Indira Hasmarini, MS. (2016)
The industrial sector, especially the trade industry plays a very important for economic activity in a country. Waroeng SS is part of the industrial restaurant or restaurant which has a very large role in promoting economic growth. This study was conducted to compare efficiency between branches of Waroeng SS Solo area using Data Envelopment Analysis (DEA). Efficiency measurement technique that uses multiple input and output is expected to measure and compare the performance between branches. Branch Waroeng SS is said to have performed efficiently if it has a score of 1 or 100% efficiency and is said to be increasingly inefficient if it is close to 0. The sample was drawn randomly by the formula slovin which then obtained a sample of 11 branches, but because there are two branches of losses in the study period, there are only nine branches that were sampled during the study period of 2014 to 2015. input period used in this study is the raw material costs, labor costs, overhead and administrative costs. Output is the total sales or turnover and net profit. The results of analysis using the DEA indicates that there are five branches whose performance has been efficient, while four other branches achieve performance that is not efficient. End of this research are suggestions for branch Waroeng SS inefficient to carry out policies that can be used to increase sales or turnover. Keywords: Waroeng SS, efficiency, Data Envelopment Analysis (DEA)